Effectiveness of the phernomone used in weevil traps Anthonomus grandis Boheman - BOLAÑO-AMAYA, RAFAEL E. (Revista Colombiana de Entomología, 1994)
The research was done to study the efectiveness of the pheromone Grandlure on the cotton boll weevil Anthonomus grandis Boheman, measure the maximum radius activity, and evaluate its presentation (Whole and Fractions). Two consecutive trials were done in a five hectares cotton field without crop residues from past seasons or ratoon cotton (soca); the experimental were located in Valledupar (Cesar) with 200 masl, 30°C of average temperature and 1160 mm average rainfall. Results show that both presentations attract the insect in a maximum radius of 100 m. It was not detected significative differences in attraction according to doses; assembly traps with any of both doses provide satisfactory results. However, whole doses in a square inch were superior in the number of individuals captured. The trap color does not influence the degree of attraction.